Curiosity's rover environmental monitoring station: Overview of the first 100 sols. Issue 7 (25th July 2014) - Gómez‐Elvira, Javier; Armiens, Carlos; Carrasco, Isaías; Genzer, Maria; Gómez, Felipe; Haberle, Robert; Hamilton, Victoria E.; Harri, Ari‐Matti; Kahanpää, Henrik; Kemppinen, Osku; Lepinette, Alain; Martín Soler, Javier; et al.
Abstract In the first 100 Martian solar days (sols) of the Mars Science Laboratory mission, the Rover Environmental Monitoring Station (REMS) measured the seasonally evolving diurnal cycles of ultraviolet radiation, atmospheric pressure, air temperature, ground temperature, relative humidity, and wind within Gale Crater on Mars. As an introduction to several REMS‐based articles in this issue, we provide an overview of the design and performance of the REMS sensors and discuss our approach to mitigating some of the difficulties we encountered following landing, including the loss of one of the two wind sensors. We discuss the REMS data set in the context of other Mars Science Laboratory instruments and observations and describe how an enhanced observing strategy greatly increased the amount of REMS data returned in the first 100 sols, providing complete coverage of the diurnal cycle every 4 to 6 sols. Finally, we provide a brief overview of key science results from the first 100 sols. We found Gale to be very dry, never reaching saturation relative humidities, subject to larger diurnal surface pressure variations than seen by any previous lander on Mars, air temperatures consistent with model predictions and abundant short timescale variability, and surface temperatures responsive to changes in surface properties and suggestive of subsurface layering.